Sep 7, 2013 Thread starter #1 S skaeno New member Sep 7, 2013 1 If τ(¬p)=1-τ(p) and τ(p∧q)=τ(p)∙τ(q) show that: τ(p∨q)=τ(p)+τ(q)-τ(p)∙τ(q)

Sep 7, 2013 Admin #2 Klaas van Aarsen MHB Seeker Staff member Mar 5, 2012 9,416 skaeno said: If τ(¬p)=1-τ(p) and τ(p∧q)=τ(p)∙τ(q) show that: τ(p∨q)=τ(p)+τ(q)-τ(p)∙τ(q) Click to expand... Hi skaeno, welcome to MHB! Perhaps you might consider that p∨q=¬(¬p∧¬q)?

skaeno said: If τ(¬p)=1-τ(p) and τ(p∧q)=τ(p)∙τ(q) show that: τ(p∨q)=τ(p)+τ(q)-τ(p)∙τ(q) Click to expand... Hi skaeno, welcome to MHB! Perhaps you might consider that p∨q=¬(¬p∧¬q)?